Supervisi Akademik Kepala Sekolah di Tinjau dari Model, Pendekatan, dan Implikasinya Terhadap Peningkatan Pembelajaran - Adimiharja Kusumadipraja; Diding Nurdin; Juliani Musti Khofifah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: Educational reform in Indonesia emphasizes student-centered learning and the development of 21st-century competencies. However, supervisory practices in many schools remain largely administrative. This study aims to map the models of academic supervision led by school principals in Indonesia and examine their reported contributions to instructional improvement. The study employed a qualitative scoping review approach following the PRISMA-ScR protocol to identify and synthesize relevant empirical studies. Article searches were conducted in the Scopus database using keywords related to principal academic supervision, instructional leadership, and school leadership in Indonesia. The initial search yielded 37 articles. After applying inclusion criteria and screening procedures, six studies were selected for final analysis. The findings reveal four dominant models of academic supervision implemented in Indonesian schools: clinical supervision, coaching-based supervision, humanistic-spiritual supervision, and collaborative supervision. These models are associated with improvements in teacher professional competence, instructional practices, and student engagement. However, several challenges persist, including limited supervisory capacity, administrative workload, and uneven institutional support. The study highlights the need to reposition academic supervision from an administrative monitoring function toward a collaborative instructional leadership practice that supports sustainable improvement in teaching and learning. Keywords: academic supervision; instructional leadership; learning quality. Abstrak: Reformasi pendidikan di Indonesia menekankan pembelajaran yang berpusat pada peserta didik serta pengembangan kompetensi abad ke-21. Dalam praktik supervisi di banyak sekolah masih cenderung berorientasi administratif. Penelitian ini bertujuan memetakan model supervisi akademik yang dipimpin oleh kepala sekolah di Indonesia serta mengkaji kontribusinya terhadap peningkatan kualitas pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan metode scoping review yang mengikuti protokol Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA-ScR). Penelusuran artikel dilakukan melalui basis data Scopus dengan kata kunci yang berkaitan dengan principal academic supervision, instructional leadership, dan school leadership in Indonesia. Tahap awal penelusuran menghasilkan 37 artikel. Setelah melalui proses seleksi berdasarkan kriteria inklusi, diperoleh enam studi yang memenuhi kelayakan analisis. Hasil sintesis menunjukkan terdapat empat model utama supervisi akademik, yaitu supervisi klinis, supervisi berbasis coaching, supervisi humanistik-spiritual, dan supervisi kolaboratif. Model-model tersebut berkontribusi terhadap peningkatan kompetensi profesional guru, kualitas praktik pembelajaran, serta keterlibatan siswa. Temuan penelitian menegaskan perlunya mereposisi supervisi akademik dari mekanisme administratif menjadi praktik kepemimpinan pembelajaran yang kolaboratif dan reflektif guna mendukung peningkatan mutu pendidikan secara berkelanjutan. Kata kunci: supervisi akademik; kepemimpinan instruksional; kualitas pembelajaran